The Associations Between Quadriceps Tendon Graft Thickness and Isokinetic Performance. Issue 4 (March 2023) - Letter, Michael I.; Parrino, Rosalia L.; Adams, Will; Ripic, Zachary; Baraga, Michael G.; Kaplan, Lee D.; Harrah, Tanner; Tremblay, Julien; Luxenburg, Dylan; Conti, Joseph; Signorile, Joseph F.
Background: Anterior cruciate ligament reconstruction (ACLR) using the quadriceps tendon is an increasingly popular technique. Both partial-thickness quadriceps tendon (PT-Q) and full-thickness quadriceps tendon (FT-Q) graft depths are employed. Hypothesis/Purpose: This study was designed to assess isokinetic peak torque, average power, and total work during knee extension in patients with FT-Q or PT-Q grafts for ACLR. We hypothesized that both groups would show lower isokinetic values for the operated side, with greater deficits in the FT-Q group than in the PT-Q group. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 26 patients who underwent ACLR with either an FT-Q or PT-Q graft were recruited between June 2021 and November 2021. Patients underwent isokinetic knee extension testing at > 1 year after surgery. Mixed repeated-measures analysis of covariance with least square difference post hoc testing was used to determine significant differences or interactions for all variables. Results: Peak torque was significantly lower for the operated limb than the nonoperated limb in the FT-Q group (mean difference [MD] ± standard error [SE], −38.6 ± 8.3 Nċm [95% CI, −55.7 to −21.5 Nċm]; P < .001; d = 0.90) but not in the PT-Q group (MD ± SE, −7.3 ± 7.7 Nċm [95% CI, −23.2 to 8.5 Nċm]; P = .348; d = 0.20). Similarly, average power for the operated limb was lower than that for the nonoperated limb in the FT-Q group (MD ± SE, −53.6 ± 13.4 W [95% CI, −81.3 to −26.9 W]; P < .001; d = 0.88) but not in the PT-Q group (MD ± SE, –4.1 ± 12.4 W [95% CI, −29.8 to 21.5 W]; P = .742; d = 0.07), and total work was lower for the operated limb compared with the nonoperated limb in the FT-Q group (MD ± SE, −118.2 ± 27.1 J [95% CI, −174.3 to −62.2 J]; P < .001; d = 0.96) but not in the PT-Q group (MD ± SE, −18.3 ± 25.1 J [95% CI, −70.2 to 33.6 J]; P = .472; d = 0.15). Conclusion: The FT-Q group showed significant deficits in the operated limb compared with the nonoperated limb for all isokinetic variables. In contrast, no significant differences were found between the nonoperated and operated limbs for the PT-Q group.